2022
DOI: 10.1039/d2qi00754a
|View full text |Cite
|
Sign up to set email alerts
|

Air-stable chiral mono- and dinuclear dysprosium single-molecule magnets: steric hindrance of hexaazamacrocycles

Abstract: Mononuclear [Dy(L1R/S)(4-Me-PhO)2](BPh4) (1R/1S) and dinuclear [Dy2(L2R/S)2(4-Me-PhO)2(OH)2](BPh4)2 (2R/2S) chiral dysprosium(III) complexes were synthesized using equatorial hexaazamacrocycle and p-cresol axial ligands. Structural and magnetic analyses reveal that 1R/1S are high-performance single-molecule magnets...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 56 publications
0
28
0
Order By: Relevance
“…Replacing Cl − with N 3 − results in shorter outer axial bond lengths and Dy⋅⋅⋅Dy distance, providing a stronger axial crystal field and intramolecular ferromagnetic coupling. It should be noted that such hula‐hoop geometry weakens the axial CF to some extent compared to D 6h symmetry, therefore constructing single N 3 − bridged all‐nitrogen‐coordinated Dy(III) SMMs by modulating the steric hindrance of the equatorial plane will be our next synthetic target [13c,26] …”
Section: Resultsmentioning
confidence: 99%
“…Replacing Cl − with N 3 − results in shorter outer axial bond lengths and Dy⋅⋅⋅Dy distance, providing a stronger axial crystal field and intramolecular ferromagnetic coupling. It should be noted that such hula‐hoop geometry weakens the axial CF to some extent compared to D 6h symmetry, therefore constructing single N 3 − bridged all‐nitrogen‐coordinated Dy(III) SMMs by modulating the steric hindrance of the equatorial plane will be our next synthetic target [13c,26] …”
Section: Resultsmentioning
confidence: 99%
“…13 Therefore, researchers adopted fine-tuning methods including the change of the coordinated solvents, ligands, electrostatic environments and pH values to explore the magneto-structural relationships. [14][15][16][17] The existence of lattice solvents can exhibit influences on Dy 2 -SMM behaviors, due to the fact that weak intermolecular interactions may fine tune the local coordination geometries of Dy III centers. 18 Moreover, the lattice solvents can adjust the intermolecular distances between the Dy III centers and further alter the dipole-dipole interactions, thus affecting the relaxation processes of Dy 2 -SMMs.…”
Section: Introductionmentioning
confidence: 99%
“…[41][42][43][44][45][46][47] The introduction of chiral information into molecular-based magnets by coordination using organic ligands that are enantiomers of each other is the most powerful strategy to construct chiral single-molecule magnets. 48,49 In 2012, Song et al reported four pairs of chiral mononuclear lanthanide complexes with double-layer sandwich structures, and they were all chiral single-ion magnets (SIMs) based on seven-coordinated lanthanide ions. 50 In 2018, Tong et al introduced a chiral binaphthyl substituent into the phthalocyanine periphery in a bis( phthalocyanine) terbium SIM, leading to bilayer molecule chirality.…”
Section: Introductionmentioning
confidence: 99%
“…53 Based on the above studies, chiral lanthanide SMMs are distributed in low-nuclearity lanthanide complexes, especially mononuclear ones. [48][49][50][51][52][53] In the high-nuclearity lanthanide cluster structure, the metal centers are densely arranged, resulting in the mutual cancellation of their magnetic axes and disorders. 8,9 SMMs based on high-nuclear lanthanide clusters are rarely reported.…”
Section: Introductionmentioning
confidence: 99%